Application of Different Standard Error Estimates in Reliable Change Methods. (15th November 2019) - Hammers, Dustin B; Duff, Kevin
Abstract: Objective: This study attempted to clarify the applicability of standard error (SE) terms in clinical research when examining the impact of short-term practice effects on cognitive performance via reliable change methodology. Method: This study compared McSweeney's SE of the estimate ( SE est ) to Crawford and Howell's SE for prediction of the regression ( SE pred ) using a developmental sample of 167 participants with either normal cognition or mild cognitive impairment (MCI) assessed twice over 1 week. One-week practice effects in older adults: Tools for assessing cognitive change. Using these SEs, previously published standardized regression-based (SRB) reliable change prediction equations were then applied to an independent sample of 143 participants with MCI. Results: This clinical developmental sample yielded nearly identical SE values (e.g., 3.697 vs. 3.719 for HVLT-R Total Recall SE est and SE pred, respectively), and the resultant SRB-based discrepancy z scores were comparable and strongly correlated ( r = 1.0, p < .001). Consequently, observed follow-up scores for our sample with MCI were consistently below expectation compared to predictions based on Duff's SRB algorithms. Conclusions: These results appear to replicate and extend previous work showing that the calculation of the SE est and SE pred from a clinical sample of cognitively intact and MCI participants yields similar values and can be incorporated into SRB reliable change statistics with comparable results. As a result, neuropsychologists utilizing reliable change methods in research investigation (or clinical practice) should carefully balance mathematical accuracy and ease of use, among other factors, when determining which SE metric to use.